FAMILY SUPPORT, MOTIVATION, AND PATIENT ADHERENCE TO TUBERCULOSIS TREATMENT: INSIGHTS FROM INDONESIA - NINDREA , Ricvan Dana; MING, Long Chia; AGUSTIAN, Dede Rahman (African Journal of Infectious Diseases (AJID), 2025)
Background: Tuberculosis (TB) remains a significant public health issue globally, with patient adherence to treatment being critical for successful outcomes. This study aimed to investigate the roles of family support and motivation in influencing adherence to TB treatment in Indonesia. Materials and Methods: A cross-sectional study was conducted among patients at four health centers in Padang Municipality, Indonesia, between January and November 2024. A total of 125 respondents diagnosed with drug-sensitive TB and in the second stage of treatment participated. Data were collected through structured interviews using validated questionnaires, assessing family support, motivation, and treatment adherence. Structural Equation Modeling (SEM) was used to analyze the relationships between variables. Results: The findings revealed significant relationships between family support and motivation (β = 0.931, t-value = 47.016, P<0.001), family support and adherence to TB treatment (β = 0.229, t-value = 2.743, P=0.006), and motivation and adherence to TB treatment (β = 0.775, t-value = 9.334, P<0.001). Conclusion: Family support and motivation play crucial roles in enhancing patient adherence to TB treatment. Strategies to strengthen family involvement and patient motivation should be integrated into TB control programs to improve treatment outcomes. Further research is recommended to explore additional factors influencing adherence in different contexts.